Laser Fusion Cutting of Stainless Steel with a Pulsed Nd:YAG-Laser - Geiger, Manfred; Gropp, Armin (Welding in the World, 1993)
Recent improvements in the beam quality and output power of Nd:YAG lasers have made them more competitive as industrial tools. Two major advantages over CO2 lasers are the increase in absorbtivity of the shorter wavelength Nd:YAG light, especially when working on metals, and the possibility of using optical fibers. This report is concerned with the influence of the main process parameters on cut quality and the optimization of cut quality when cutting thin section stainless steel with an inert gas using a pulsed Nd:YAG laser.
LFT Import::2019-07-15 (398)